KINERJA PEGAWAI: BUDAYA ORGANISASI DAN MOTIVASI KERJA MELALUI KEPUASAN KERJA PEGAWAI - Bima Wahyu Hermananta; Taufiq Noor Rokhman; Nurrokhman Wobowo (Jurnal Manajemen Dan Akuntansi Medan, 2023)
An organization whether it is profit and public services are required to be able to show their best performance consistently in order to achieve organizational goals. One of the factors that determine the achievement of organizational goals is the performance of human resources. The purpose of this study was to analyze the influence of organizational culture and work motivation on job satisfaction and employee performance. In accordance with the subject matter and purpose of the research that has been formulated, then this kind of research is explanatory research. The sample in this study was 103 employees. The analytical tool used is path analysis. Based on the analysis of evidence that organizational culture and work motivation influence on job satisfaction, organizational culture, motivation and job satisfaction influence on employee performance. Job satisfaction may mediate the influence of organizational culture and work motivation on employee performance. In order to improve employee performance, Institutions need to create a good organizational culture that is applied on the ability of the completion of the work, in addition, employees need to be motivated more by policies decided upon as creating a conducive working environment, providing fasiitas and facilities that support, and more consider the form of awards for employees